The Effectiveness of Hook Techniques in Hand Wrestling in POGTI Athletes in Semarang City - Muhammad Syahrul Sefianto; Fajar Awang Irawan (STKIP Taman Siswa Bima, 2026)
The hook technique in arm wrestling requires optimal coordination, strength, and joint stability; however, improper execution may reduce effectiveness and increase injury risk. This study aimed to analyze the biomechanical effectiveness of the hook technique performed by athletes from the Indonesian Arm Wrestling Sports Association (POGTI) in Semarang. A quantitative descriptive approach was used involving 10 elite athletes selected purposively. High-speed video analysis using Kinovea software (version 0.9.5) measured key kinematic variables, including wrist flexion, elbow angle, shoulder angle, and shoulder distance across the preparation, execution, and completion phases. The results revealed a consistent biomechanical pattern, indicated by a significant decrease in wrist angle from 173.12° ± 4.54° during preparation to 91.40° ± 27.00° at completion, showing the dominance of the cupping mechanism. Shoulder distance remained stable at 24–26 cm, reflecting adherence to the chain principle, which supports optimal force transfer and injury prevention. These findings confirm that the hook technique applied by POGTI Semarang athletes aligns with global biomechanical standards in terms of efficiency and safety. Therefore, it is recommended to incorporate wrist flexor strengthening and isometric elbow training to further enhance performance and reduce injury risk.